2020
DOI: 10.1111/tpj.14815
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling of wild‐type and mutant soybean root nodules using laser‐ablation electrospray ionization mass spectrometry reveals altered metabolism

Abstract: SUMMARY The establishment of the nitrogen‐fixing symbiosis between soybean and Bradyrhizobium japonicum is a complex process. To document the changes in plant metabolism as a result of symbiosis, we utilized laser ablation electrospray ionization‐mass spectrometry (LAESI‐MS) for in situ metabolic profiling of wild‐type nodules, nodules infected with a B. japonicum nifH mutant unable to fix nitrogen, nodules doubly infected by both strains, and nodules formed on plants mutated in the stearoyl‐acyl carrier prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 113 publications
2
22
2
Order By: Relevance
“…Metabolic profiling has been used to study metabolic shifts in SNF associations. Recently, metabolic profiling were performed on effective and ineffective nodules of soybean to identify the active processes according to the partners involved in the symbiosis (Agtuca et al, 2020). Metabolite levels were determined to characterize the different plant phenotypes and interactions with rhizobia.…”
Section: Metabolic Modeling and Metabolic Profiling Studies On Legumementioning
confidence: 99%
“…Metabolic profiling has been used to study metabolic shifts in SNF associations. Recently, metabolic profiling were performed on effective and ineffective nodules of soybean to identify the active processes according to the partners involved in the symbiosis (Agtuca et al, 2020). Metabolite levels were determined to characterize the different plant phenotypes and interactions with rhizobia.…”
Section: Metabolic Modeling and Metabolic Profiling Studies On Legumementioning
confidence: 99%
“…These specialized root organs have several visually and functionally distinct compartments (i.e., outer cortex, sclerenchyma, inner cortex, and infection zone), where a population of root cells is infected with nitrogen-fixing soil bacteria (Rhizobiaceae) (Livingston et al, 2019 ). Using the MALDI-MSI (Velickovic et al, 2018 ) and other MSI modalities (Agtuca et al, 2020 ; Samarah et al, 2021 ), we recently spatially resolved critical metabolic and lipidomic pathways in different compartments of soybean root nodules, and also showed different metabolic profiles in infected and uninfected plant cells inside the infection zone (Samarah et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that the relative abundance of fatty acids, purines, and lipids was changed significantly in response to the symbiosis. Agtuca et al, 2020 analyses of protein levels through proteomics technique are more essential for deciphering complex molecular mechanisms in plant-bacteria associations, especially as it applies to BGNbacteria interactions. Therefore, identification of other proteins involved in plant beneficial interactions through proteomics analysis of BGNbacteria interaction is an avenue to harness the capacity of these beneficial bacteria on BGN yield.…”
Section: Glycine Max Bradyrhizobium Japonicummentioning
confidence: 99%